How to diagnose and treat patients with inflammatory bowel disease - Sokić-Milutinović Aleksandra (Pharmaceutical Association of Serbia, Belgrade, Serbia, 2017)
Inflammatory bowel diseases (IBD) are idiopathic, chronic intestinal inflammatory diseases. IBD pathogenesis is related to altered immune response and its complex interaction with gut microbiota, genetic and environmental factors. Most common types of IBD are ulcerative colitis (UC) and Crohns disease (CD), while a subset of patients suffer from undetermined IBD. Ulcerative colitis is chronic inflammatory disease limited to colonic musoa. As opposed to UC, CD is chronic granulomatous disease that can affect any segment of the gastrointestinal tract and all layers of bowel wall. Extraintestinal manifestations of IBD include musculoskeletal, dermatological, ocular and hepatobiliary manifestations. IBD diagnosis is based on clinical presentation, laboratory findings, endoscopic procedures with patohistological examination of tissue biopsies. In some patients additional radiographic diagnostic tools are needed. Therapy in IBD patients is based on the use of mesalamines and sulphasalazyne, corticosteroids, immunomodulators, biologic therapy and surgery. Mesalamines are used as induction therapy in UC patients, while corticosteroids and biologic therapy can be used as induction therapy in both UC and CD patients. Maintenance therapy in UC consists of mesalamines, thiopurines and biologics, while in CD thiopurines, methotrexate and biologics can be used. In pediatric patients nutritional therapy can be beneficial.